2020
DOI: 10.3390/w12051349
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sedimentin Yellow River on Hydraulic Characteristics of Spray Sprinkler

Abstract: The water shortage has become a great challenge for Yellow River irrigation regions; for the high level of suspended sediment in Yellow River, sprinkler irrigation, which has achieved superior anti-clogging performance, can be an effective solution for water conservation in agriculture management. For the direct utilization of the Yellow River water resource in irrigation land as irrigated by movable sprinkler irrigation systems, a series of experiments about the effect of sediment-water on the hydraulic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Zhang et al (2020) also found a reduction in the internal coating of a sprinkler irrigation system pipeline due to corrosion. The authors report that this phenomenon was triggered by the transport of the water solution in the pipes and emphasize the relevance of new research related to the subject, especially regarding the useful life and uniformity of water distribution in the system.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Zhang et al (2020) also found a reduction in the internal coating of a sprinkler irrigation system pipeline due to corrosion. The authors report that this phenomenon was triggered by the transport of the water solution in the pipes and emphasize the relevance of new research related to the subject, especially regarding the useful life and uniformity of water distribution in the system.…”
Section: Resultsmentioning
confidence: 97%
“…This recommendation is because the corrosion and consequent exchange of materials cause financial disruption and setbacks (Dixon & Liu, 2020;Parthipan et al, 2017), in addition to possible water stress and crop damage, which can affect agricultural production. Zhang et al (2020) also found a reduction in the internal coating of a sprinkler irrigation system pipeline due to corrosion. The authors report that this phenomenon was triggered by the transport of the water solution in the pipes and emphasize the relevance of new research related to the subject, especially regarding the useful life and uniformity of water distribution in the system.…”
Section: Estimated Thickness Loss and Useful Life Expectancy Of Speci...mentioning
confidence: 94%
“…Therefore, it is necessary to further study the error of the metering device for muddy water pipeline irrigation by combining these factors. It is helpful to protect and maximize the utilization of the Yellow River resource with superior hydraulic performance that can be used for agricultural irrigation [40].…”
Section: Discussionmentioning
confidence: 99%